Cover Feature: Origin of Hydrocarbons Stability from a Computational Perspective: A Case Study of Ortho‐Xylene Isomers (ChemPhysChem 6/2020). Issue 6 (16th March 2020) - Mitoraj, Mariusz P.; Sagan, Filip; Szczepanik, Dariusz W.; de Lange, Jurgens H.; Ptaszek, Aleksandra L.; van Niekerk, Daniel M. E.; Cukrowski, Ignacy
Abstract : The Cover Feature demonstrates, contrary to the intuition and classical steric‐based perception, the CH⋅⋅⋅HC attraction in ortho‐xylene rotamers. It is revealed, that their stability is rooted in cooperative action of hyperconjugation, aromaticity and intra‐molecular "bay and side‐types" CH⋅⋅⋅HC interactions. More information can be found in the Article by M P. Mitoraj et al. on page 494 in Issue 6, 2020 (DOI: 10.1002/cphc.202000066 ).